2005
DOI: 10.1007/s00438-005-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of 5S rRNA in Saccharomyces cerevisiae

Abstract: Abstract5S rRNA extends from the central protuberance of the large ribosomal subunit, through the A-site finger, and down to the GTPase-associated center. Here, we present a structure-function analysis of seven 5S rRNA alleles which are sufficient for viability in the yeast Saccharomyces cerevisiae when expressed in the absence of wild-type 5S rRNAs, and extend this analysis using a large bank of mutant alleles that show semidominant phenotypes in the presence of wild-type 5S rRNA. This analysis supports the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 67 publications
3
36
0
1
Order By: Relevance
“…To choose among the numerous allelic variants of human 5S rRNAs reported to date (Kiparisov et al 2005), we performed RT-PCR and sequenced 5S rRNAs isolated from HeLa cells or from purified mitochondria. In both cases, the same 5S rRNA sequence was found to be the most abundant and was thus chosen for further experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To choose among the numerous allelic variants of human 5S rRNAs reported to date (Kiparisov et al 2005), we performed RT-PCR and sequenced 5S rRNAs isolated from HeLa cells or from purified mitochondria. In both cases, the same 5S rRNA sequence was found to be the most abundant and was thus chosen for further experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, 5S rRNA seems to be one of the most interesting RNA species from the point of view of its intracellular traffic, which implicates a network of possible itineraries for various subcellular localizations. Being an integral part of large ribosomal subunit of almost all living organisms, it appears to perform a very important function in the translation process, as recent evidence suggests Kiparisov et al 2005;Kouvela et al 2007). At the same time, it was shown that, at least in Xenopus laevis oocytes, to integrate a ribosome, a 5S rRNA molecule has to be first exported from the nucleus by the transcription factor IIIA (TFIIIA) (Pelham and Brown 1980;Guddat et al 1990) and reimported into the nucleolus with the ribosomal protein L5; the 5S rRNA-L5 complex is then involved in the central protuberance formation (Steitz et al 1988;Rudt and Pieler 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Purified ribosomes were treated with 1 mM puromycin and 1 mM GTP for 30 minutes at 37°C to remove aa-tRNAs and elongation factors. Treated ribosomes were then incubated with DMS as previously described (25). RNAs isolated from DMS-treated and untreated cells and ribosomes were annealed with 32 P-end-labeled primers (Table 2) by incubation at 70°C followed by slow cooling and holding for 5 min to 40°C followed by immediate transfer to ice.…”
Section: Methodsmentioning
confidence: 99%
“…Inset graphs indicate the fold changes in doubling times of the mutants in the presence of increasing drug concentrations normalized to that of wild-type cells under the same conditions. Sparsomycin lethal dose (g/ml) 25 …”
Section: Specific Repression Of ؊1 But Not ؉1 Prfmentioning
confidence: 99%
“…sap., H. sapiens. (C) The S. cerevisiae cytoplasmic 5S rRNA secondary structure (15,53) showing the position of the ⌿.…”
Section: Resultsmentioning
confidence: 99%